The 1/N expansion of colored tensor models - Gurǎu, Rǎzvan (Annales Henri Poincaré, 2011)
In this paper, we perform the 1/N expansion of the colored three-dimensional Boulatov tensor model. As in matrix models, we obtain a systematic topological expansion, with increasingly complicated topologies suppressed by higher and higher powers of N. We compute the first orders of the expansion and prove that only graphs corresponding to three spheres S3 contribute to the leading order in the large N limit.
Gesehen am 07.10.2022